The Role of Sport in Reducing Racism and Its Relation to Social Acceptance in the Movie The Blind Side - Siwi, Galih Ratna (LANTERN (Journal on English Language, Culture and Literature), 2013)
Film is the example of literary works which reflects the social issues that occur in a society. The writer is interested to analyze the social issue in The Blind Side. In this case, the writer intends to examine the role of sport in reducing racism that occur to an African American who lives in Tennessee, The United States of America. It also concerns his existence in the Whie American society in which its people have different skin colors. The writer uses two elements to analyze this thesis. They are intrinsic and extrinsic elements. The intrinsic aspect given in this thesis consists of two aspects, namely narrative aspect which includes character, setting, and conflict; cinematography aspect which includes shot size and sound. The writer uses racism and sport theory, where concept consists of stereotype, prejudice, dan discrimination. The Blind Side reflects the effects of racism towards an African American’s existence in the mid of the white society. His struggle makes him accepted not only by his schoolmates but also by the society. Based on the explanation above, it is revealed that racism that occurs to an African American can be annihilated by his achievement in sport, in this case, football. Keywords: racism, football, social acceptance, African American